2014
DOI: 10.7589/2013-10-275
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE OF ANOXYSPIRURA PETROWIEPIZOOTIC IN NORTHERN BOBWHITES (COLINUS VIRGINIANUS), TEXAS, USA

Abstract: ABSTRACT:We captured 36 Northern Bobwhites (Colinus virginianus) in Mitchell County, Texas in June-September 2013, and examined them for the eyeworm Oxyspirura petrowi. We recovered 334 eyeworms from 28 of 29 adult bobwhites (97%); infections ranged from 1-40 worms and mean (6SD) abundance of 11.9613.0. Three of seven juveniles were infected, and those infected had one eyeworm each. Prevalence of eyeworms was similar among months. However, mean abundance of eyeworms peaked in July and August (3.362.1, 13.5615.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 12 publications
4
73
0
Order By: Relevance
“…have been reported from more than 80 avian species worldwide [1]. Oxyspirura petrowi has recently received increased attention because of high prevalences detected in declining native Galliformes populations in North America [2,3]. Oxyspirura petrowi has a broad host range and has been reported infecting birds in the order Passeriformes and Galliformes [2,4–6].…”
Section: Introductionmentioning
confidence: 99%
“…have been reported from more than 80 avian species worldwide [1]. Oxyspirura petrowi has recently received increased attention because of high prevalences detected in declining native Galliformes populations in North America [2,3]. Oxyspirura petrowi has a broad host range and has been reported infecting birds in the order Passeriformes and Galliformes [2,4–6].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have also shown that increased parasite loads can correlate with the host population decline and reduced parasite loads throughout the populations correlate with an upward trend in the host population [20]. Eyeworm infection rates in northern bobwhites of the Rolling Plains region of Texas have been reported at greater than 90% in sampled birds and there is concern that the population of bobwhites is declining [4].…”
Section: Discussionmentioning
confidence: 99%
“…Oxyspirura petrowi has been receiving increased attention due to its potential role in negatively impacting gamebirds [4]. This parasite, known as the eyeworm, is a nematode that lives on the surface of and/or behind the eyeball in the lacrimal duct and its associated glands.…”
Section: Introductionmentioning
confidence: 99%
“…All There was no evidence of gross pathology in Northern Bobwhites, despite heavy infection of O. petrowi in the nasal-lacrimalorbital tissue accompanied by spot hemorrhaging and inflammation (Dunham et al 2014). This same report documented eyeworms attached to tissue, which suggests they were ingesting blood.…”
mentioning
confidence: 82%
“…Eyeworms were found in greater than 90% of bobwhites trapped on the ranch (Dunham et al 2014). Three Northern Mockingbirds and one Curve-billed Thrasher were captured using doublefunnel, welded wire, walk-in traps (91.4361.0320.3 cm) baited heavily with milo.…”
mentioning
confidence: 99%